Towards an observer/controller and ontology/rule-based approach for pervasive healthcare systems. (2017) - HameurLaine, Amina; Abdelaziz, Kenza; Roose, Philippe; Kholladi, Mohamed-Khireddine
This paper proposes a new design approach for U-Healthcare systems. Our approach consists in combining the generic observer/controller architecture of organic computing, ontologies and rule-based paradigms. This combination brings three significant benefits. First, it allows keeping the system highly supervised and controlled by the observer/controller. Secondly, it enables the system to reason upon useful contextual information gathered from different and heterogeneous entities, and deduce new situations that require adaptation of the system's behaviour. Finally, it enables the system to adapt its behaviour dynamically to the context change by reasoning about this context and selecting the appropriate service to a specific user.